Recepcja motywów antycznych we współczesnej sztuce na przykładzie twórczości artystów: Léo Caillarda i Ayali Serfaty - Michalska, Adriana (Collectanea Philologica, 2018)
The objective of this article is to define place and role of antique motives in modern art and design. Due to variety of creativness in XX/XXI century, created in different trends and beyond them, considerations were limited to sculptural art and design, based on creativness of French artist Léo Caillard and Israeli designer Ayala Serfaty. Interpretation of information, which was collected based on study of artists’ works of art, lead to conclusion that, despite different approach to antique tradition, both artists strive to similar targets and their intention is not imitation, but concept based on creation of surprising or even shocking links and juxtapositions. Research of contrasts between tradition and modernity is intended to provoke and encourage viewer to deeper and conscious interpretation of works of art and reflection about position of art in modern culture. It is essential to study esthetic contexts, circumstances of creation of works of art and motivation. The most important feature of this art is to induce strong impressions. Relations between viewer and work of art have crucial meaning. Approximation and logic of thinking, which are characteristic for each research orientations in history of classic and modern art, represents theoretical background of this article. In this context, there are references to Joachim Winckelmann, recognized as creator of methodological basics for researchment on ancient art. There are references to Franz Wickhoff, Aby Warburg and Erwin Panofsky who dealt with iconographical and iconographical-iconological methods.